KAJIAN SEMIOTIKA PADA VISUALISASI TOKOH ALL MIGHT DALAM MANGA BOKU NO HERO ACADEMIA SEBAGAI REPRESENTASI SUPERHERO AMERIKA - I Gusti Bagus Bayu Baruna Ariesta; Made Vairagya Yogantari; Anak Agung Ngurah Bagus Kesuma Yudha (Jurnal Nawala Visual, 2019)
Delivering a story through visual comic characters can make it easier for readers to understand the contents and distinguish one character from another. Not only as a distinguishing element, but visualization of comic characters can represent areas where the visual is commonly used and found. In the comic titled Boku No Hero Academia (BNHA) found elements and terms that are commonly found in comics and American superhero characters in general, one of them through the All Might character. Through qualitative research methods, with data collection techniques through observation, literature, and internet studies, this paper aims to examine how the characters of All Might represent American superheroes through his visuals.